Economic Vitality of Communities for Urban Development: the Case of the Cities from Country of Small Economy - Jurgita Bruneckiene; Jolita Sinkiene; Egle Gaule; Ineta Zykiene (Institute of Economic Research (IER), 2017)
Economic vitality of community is one of the main factors and conditions for successful urban development. The article present the theoretical and empirical analysis of the concept of economic vitality of urban community in the country of small economy. The objective of the paper is to identify the challenges and factors of improving the economic vitality of community in cities of a country with a small economy and to develop the strategic recommendations and measures for strengthening the economic vitality of the community. Methods used: literature studies, document analysis, statistical data analysis, expert interview, survey, case analysis, Space Syntax analysis. The research showed that the communities in the country of small economy are still not entrepreneur and economically vital; there's a lack of cooperation cultural and experience among of communities and businesses; there are favorable conditions to promote community (economic) vitality. Strategies to encourage and facilitate business and community cooperation at the local government level are necessary. Communities and companies are ready to cooperate together, but the cooperation based on shared value is not grown up yet. The article concludes with recommendations for promotion the vitality of communities and cooperation with business.
Keywords: R11; P32; P35; 330; economic vitality; community; cities; urban economic development